2016
DOI: 10.4238/gmr.15017496
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of epithelial ovarian cancer reveals key genes and pathways associated with chemotherapy resistance

Abstract: ABSTRACT. The aim of this study is to analyze gene expression data to identify key genes and pathways associated with resistance to platinumbased chemotherapy in epithelial ovarian cancer (EOC) and to improve clinical treatment strategies. The gene expression data set was downloaded from Gene Expression Omnibus and included 12 chemotherapy-resistant EOC samples and 16 chemotherapy-sensitive EOC samples. A differential analysis was performed to screen out differentially expressed genes (DEGs). A functional enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For example, IL6, HIST1H3C, and HIST1H3G, which were classified with high degrees are present in pathways associated with transcriptional dysregulation in cancer. In addition, these three genes have been previously reported to be closely associated with tumorigenesis and development [7173].…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL6, HIST1H3C, and HIST1H3G, which were classified with high degrees are present in pathways associated with transcriptional dysregulation in cancer. In addition, these three genes have been previously reported to be closely associated with tumorigenesis and development [7173].…”
Section: Discussionmentioning
confidence: 99%
“…We performed gene ontology (GO) bioinformatics analysis on the differentially expressed proteins with a 1.5-fold change to catalog the molecular functions, cellular components and biological processes [ 26 ]. The enrichment analysis of the proteins was conducted with all proteins GO biological processes database information from our study using the following formula [ 27 ]: where N is the number of all proteins within the GO annotation information, n is the number of differentially regulated proteins within GO annotation information, M is the number of proteins for a given GO annotation, and m is the number of differentially regulated proteins following a given GO annotation. Significant GO enrichment was defined as P ≤ 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies performed in cancer tissues from patients point toward an oncogenic role of RTN3, as it was shown that increased RTN3 levels are observed in astrocytoma whereas no expression was observed in healthy glial cells (Huang et al, 2004 ). Furthermore, RTN3 was one of the top three upregulated genes in chemotherapy-sensitive epithelial ovarian cancer samples pointing toward an anti-tumor role under these conditions (Zhang and Luo, 2016 ). These findings highlight the need for tight regulation of selective autophagy components within the tumor microenvironment.…”
Section: Selective Autophagy Components In Cancermentioning
confidence: 99%